Electronic information sharing between public universities and ministry of higher education and scientific research: A pilot study - Mohammed, Mohammed; Ibrahim, Huda; Mohd Nadzir, Maslinda (2015)
Many institutions in the higher education sector use electronic information sharing to enhance their services and decision making.Ministry of Higher Education and Scientific Research (MOHESR) in Iraq has adopted electronic information sharing to provide better services.However, the electronic information sharing system among universities and MOHESR is limited.In this study, a theoretical framework that includes the influencing factors of electronic information sharing was proposed to enhance the electronic information sharing among them.A questionnaire was designed to examine the hypothesis for each factor.To verify the reliability of the questionnaire, a pilot study was done twice.The first one was observed low value for three factors. However, the values obtained through a second study were accepted.